Chlorophyll fluorescence and other physiological parameters as indicators of waterlogging and shadow stress in lulo (Solanum quitoense var. septentrionale) seedlings (2019)
Climate change has resulted in an increasing frequency of the phenomenon “La Niña,” generating prolonged periods of waterlogging and low light. The objective of the present study was to evaluate the effects of two abiotic stresses: shading (65%) and waterlogging, and their interaction on fluorescence parameters of chlorophyll a in lulo (Solanum quitoense var. septentrionale) seedlings. A completely randomized design with a factorial arrangement was implemented. The first factor consisted of two levels of light (with and without shading). The second factor were four levels of duration of the waterlogging period (0, 3, 6 and 9 days), for a total of 8 treatments with three replicates. The response variables were recorded at 6, 12 and 18 days after the application of the waterlogging treatments began. Measurements of relative water content (RWC), electrolyte leakage, chlorophyll content and chlorophyll a fluorescence were recorded. The lulo plants appeared to be more susceptible to waterlogging than to shading, with a lower RWC when waterlogged 6 and 9 days, presenting damage at the level of photosystem II from day 3, causing a decrease in the chlorophyll content. The plants flooded under shading had a greater tolerance to this factor than those cultivated in full light. The techniques of quantification of the chlorophyll a fluorescence, especially the maximum quantum efficiency of the PSII, the effective photochemical quantum yield of PS II and the photochemical quenching were useful tools that characterized the lulo seedlings under stress conditions.